Success Rate Padat Karya Paving Geprek Program’s For Poor Families In Surabaya City - Azizah, Nadifa Afni; Wibawani, Sri (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
The impacts of Pandemi Covid-19 such as poverty and unemployment. However, the number of poor people and the unemployment rate in the city of Surabaya decreases every year. This means that the Surabaya City Government has attempted to provide a solution by establishing community empowerment programs such as labor-intensive programs for poor families. One example is Padat Karya Paving GePREK (Mutual Cooperation, Empowerment and Community Economy). This program has been implemented in 10 sub-districts out of 31 sub-districts in the city of Surabaya. Therefore, this research aims to measure the success of the Padat Karya Paving GePREK for Poor Families in the City of Surabaya using a quantitative method with a descriptive approach of one variable, namely the success of the program is measured by indicators of the objectives of the padat karya in accordance with Surabaya Mayor Regulation Number 83 of 2023 concerning Padat Karya Programs in the City of Surabaya. Data was obtained through questionnaires, interviews and documentation. This research consisted of 79 respondents. The research results, this program was considered successful in achieving program objectives with a percentage of 63%.